Pengaruh Tingkat Konsentrasi Nutrisi Cair Landetox Hijau dan Lama Penyimpanan Biji terhadap Pertumbuhan Bibit Leci (Litchi chinensis, Sonn) - Hukom, Zakarias F M; Makaruku, Marlita H; Kokoreukap, Fifi (Fakultas Pertanian, Universitas Pattimura, 2025)
The production of lychee seedlings as a source of rootstock in plant propagation techniques by grafting is very rare. Lychee seeds are recalcitrant seeds, so they are prone to deterioration in seed quality after harvest. The longer the storage time of lychee seeds after harvest, the greater the decline in the quality of the lychee seedlings. Landetox Green liquid nutrition is one type of plant nutrition that is specially made to stimulate the vegetative growth of plants. The use of the right level of Landetox Green liquid nutrient concentration has an effect on the growth of quality lychee seedlings. The purpose of this study was to determine the combination of treatment levels of liquid nutrient concentrations of Green Landetox and the appropriate storage time for seeds after harvest to increase the growth of lychee seedlings in the nursery.